Use of honey associated with Ananas comosus (Bromelin) in the treatment of acute irritative cough - Décio Medeiros Peixoto; José Angelo Rizzo; Deborah Schor; Almerinda Rêgo Silva; Dinaldo Cavalcanti de Oliveira; Dirceu Solé; Emanuel Sarinho
Abstract Objective: To evaluate the immediate improvement rate of irritative cough in patients treated with the combination of Ananas comosus extract and honey (Bromelin®) compared with the use of honey alone (placebo group). Methods: Pragmatic, double-blind, randomized, parallel-group study with children aged between 2 and 15 years, with irritative cough for at least 24hours. The double-blind assessment of cough was through the number of observed coughing episodes and intensity score for a period of 10minutes of observation. The decrease of one point in the mean total score was considered as a therapeutic effect. Results: There was a reduction in coughing episodes in both groups, as well as in the cough score after 30minutes of drug or honey administration. The change in clinical score above two points, which could indicate marked improvement, occurred in five patients in the bromelin group and only in one in the placebo group, but without significant difference. There were no adverse events. Conclusions: The immediate improvement rate of irritative cough was similar in patients treated with combination of Ananas comosus extract and honey (Bromelin®) compared with the use of honey alone (placebo group). It is possible that honey has a therapeutic effect on mucus and cough characteristics (Clinical Trials: NCT01356693).